Analisis Struktur Perekonomian Berdasarkan Pendekatan Input- Output di Provinsi Jawa Timur - Endah Kurnia Lestari; Olvi Mifta Alfiatul Jannah (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
This study aims to (1) discover the shift of economic structure of East Java Province period 2010 and 2015; (2) to identify the various leading sectors in economic development in East Java Province Period 2010 and 2015. The analysis method used in this research is quantitative descriptive by using the Input-Output approach. The linkages between sectors of the economy, leading sectors, and economic sector multipliers have widely used to analyze this approach. Furthermore, structural shifts are analyzed using a multiplier product matrix (MPM) that can describe the landscape of an economy. The results showed that based on the analysis of MPM has not occurred a shift in economic structure significantly. However, there has been a change in the tertiary sector. Although until now, the economy of East Java Province is still dominated by the secondary industry. The leading industry of East Java Province is owned by the manufacturing industry, although there are other potential sectors as the leading sector.